ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BENTUK ALJABAR - Muamar Abiyoga; Ade Rohayati (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to describe students' mistakes in solving algebraic calculation operation problems in class VII and analyze aspects that cause students to make mistakes. This type of research is included in qualitative descriptive research. The subject of the research is a grade VII student of SMP IT Alhimmah. The data collection methods used in this study are tests, interviews and documentation. Data analysis techniques through data reduction, data presentation and conclusions. Based on the results of the study, it can be concluded that the mistakes made by students in solving algebraic calculation operations include: (1) Misunderstanding of problems; (2) Errors in understanding and applying concepts; (3) Calculation errors. The aspects that cause students to make mistakes are that students do not understand the purpose of the questions given, students have not mastered the prerequisite material, students do not understand the material, students forget basic algebraic formulas and concepts, students lack practice in solving algebra and arithmetic operations, students are less thorough when performing calculation operations, and students do not double-check the completed answers.